Pendapat Mahasiswa terhadap Implementasi PBL pada Kurikulum Berbasis Kompetensi Program Studi S1 Keperawatan - Richa Noprianty (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: New paradigm in health profession education caused exchange of medical education curriculum from conventional to Competency Based Curriculum (CBC). One teaching methode of competence-based curriculum implementation is Problem Based Learning (PBL). PBL was impemented in Bachelor of Nursing Programme STIKes Dharma Husada Bandung since 2010. This research aim was to analyse students opinion about the implementation of Problem Based Learning (PBL) for Bachelor phase of Nursing Programme in STIKes Dharma Husada Bandung.Method: This research was cross sectional study using questionnaires to students of level 2 and 3 Bachelor of Nursing. Total 114 students out of a population of 160 students (with stratified random sampling) involved in this study. Results: This study showed that most students (85.1%) gave positive opinion on PBL if socialized in the beginning of learning process. Scenario has stimulated the students as much as 71.1%, and the role of moderator and secretary duties as much as 77.2%, while skills lab instructors imprecise 50% weighting in accordance with the duties of assessment, there are 41.2% who disagree and knowledge becomes widely agreed as much as 77.2% of studentsConclusion: Most of the students gave positive opinion on PBL socialization in the beginning of the learning process. About 50% students felt skills lab instructor usually hard to be on-time and the literatures provided were not sufficient.